Шевченкові візії ідеального суспільства (на матеріалі триптиха «Молитва») - Клочек, Г. (Слово і Час, 2022)
У статті висвітлено обставини створення, ідейно-художні особливості триптиха Тараса Шевченка «Молитва». Якщо в перших двох віршах циклу поет звертався до Бога з проханням покарати експлуататорів («царів» та «шинкарів»), то в третій поезії він відмовився від такого радикалізму і прохав зупинити тих, хто творить зло. Т. Шевченко вважав, що так можна досягти соціального примирення. Пафос ствердження гармонійності світобудови акцентовано в останній поезії триптиха: молитва зазвучала як гімн, що прославляє красу суспільства, в якому поєднана соціальна справедливість, працьовитість й освіченість народу, висока моральність і любов. The author offers the new interpretative version of reading Taras Shevchenko’s triptych “Prayer” (“Molytva”). Based on the memoirs, the process of creating the triptych is shown in detail. Taras Shevchenko created three variants of the poetry in sequence, and each one had the character of a prayer to God with requests to make life happier and social order fairer. In order to trace the changes, which took place in the evolution of poetic meanings in each new piece of the triptych, to understand their logic and intention, all three poems were analyzed. The poet’s prayer concerns the process of shaping an ideal society on the basis of its internal harmonization. In the first two poems of the cycle, Shevchenko appealed to God with requests of punishment for the exploiters (‘tsars’ and ‘taverners’), and then in the third poetry, he abandoned such radicalism and asked to stop those who do evil things. He believed that social reconciliation could be achieved. The third poetry of the cycle is a complete, final version. We can assume that the previous two poems of the triptych are draft s that have survived thanks to Oleksandr Lazarevskyi, who wrote them down in “Bigger Book”. However, the presence of these “draft s” allows us to trace the creative process of forming a vision of a perfect, internally harmonized social order. The pathos of the assertion of the universal harmony has acquired a special rise in the last poem of the triptych. The prayer sounded like a hymn glorifying the beauty of society in which social justice, diligence, and education of the people, high morality and love are harmoniously combined. The analysis revealed one of the facets of Taras Shevchenko’s ingenious intellectual insight into the essence of things and phenomena. Several days of literary work in May 1860 ended up with the creation of a prayer for the society of the future, the internal harmony of which is absolute.